2017
DOI: 10.1080/02688697.2017.1297766
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous cerebrospinal fluid rhinorrhoea with meningitis secondary to ecchordosis physaliphora

Abstract: Transclival CSF fistulae are rare. We report a 40-year-old female who presented with meningitis after a short history of CSF rhinorrhoea. The defect resulted from the rare notochordal remnant, ecchordosis physaliphora (EP), and was successfully resected and repaired endoscopically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…A literature review in 2013 identified 23 case reports of symptomatic EP 29 and our literature search revealed an additional 8 cases. 24 30 31 32 33 34 35 Symptoms included diplopia, cranial nerve VI palsy, facial dysesthesia, headache, confusion, dizziness, hearing loss, tinnitus, facial pain, hemiparesis, and sudden death due to intratumoral bleed. 25 36 The reported cases also include six cases of rhinorrhea secondary to spontaneous CSF fistula.…”
Section: Discussionmentioning
confidence: 99%
“…A literature review in 2013 identified 23 case reports of symptomatic EP 29 and our literature search revealed an additional 8 cases. 24 30 31 32 33 34 35 Symptoms included diplopia, cranial nerve VI palsy, facial dysesthesia, headache, confusion, dizziness, hearing loss, tinnitus, facial pain, hemiparesis, and sudden death due to intratumoral bleed. 25 36 The reported cases also include six cases of rhinorrhea secondary to spontaneous CSF fistula.…”
Section: Discussionmentioning
confidence: 99%
“…Previous cases report that the endoscopic endonasal transsphenoidal approach can be used to successfully manage the following complications associated with EP, including repair of clival defects [6,8,9,14,15], management of CSF leaks [6,9,14,15], and decompression of the abducens nerve [14,20]. An endoscopic endonasal approach is not always indicated for clival EP.…”
Section: Discussionmentioning
confidence: 99%
“…An MRI with contrast was obtained and compared with the previous CT and MRI examinations. Imaging ration and extension into the sphenoid sinus [2,3,[6][7][8][9]. The migration of notochord tissue explains the potential for physaliphorous cells to be found in the extradural, subdural, and subarachnoid spaces [2,3,6].…”
Section: Case Presentationmentioning
confidence: 99%
“…However, there are several case reports describing symptomatic ecchordosis physaliphora as well. The most common symptoms include headache, pneumocephalus, spontaneous cerebrospinal fluid (CSF) rhinorrhea with meningitis, and abducens nerve palsy [3][4][5][6][7]. The differential diagnoses of retroclival intradural lesions consist mainly of chordoma, ecchordosis physaliphora, skull base metastasis, dermoid cyst, epidermoid cyst, and arachnoid cyst.…”
Section: Introductionmentioning
confidence: 99%